ZNRF1 Mediates Epidermal Growth Factor Receptor Ubiquitination to Control Receptor Lysosomal Trafficking and Degradation - Shen, Chia-Hsing; Chou, Chih-Chang; Lai, Ting-Yu; Hsu, Jer-En; Lin, You-Sheng; Liu, Huai-Yu; Chen, Yan-Kai; Ho, I-Lin; Hsu, Pang-Hung; Chuang, Tsung-Hsien; Lee, Chih-Yuan; Hsu, Li-Chung (Frontiers in Cell and Developmental Biology, 2021)
Activation of the epidermal growth factor receptor (EGFR) is crucial for development, tissue homeostasis, and immunity. Dysregulation of EGFR signaling is associated with numerous diseases. EGFR ubiquitination and endosomal trafficking are key events that regulate the termination of EGFR signaling, but their underlying mechanisms remain obscure. Here, we reveal that ZNRF1, an E3 ubiquitin ligase, controls ligand-induced EGFR signaling via mediating receptor ubiquitination. Deletion of ZNRF1 inhibits endosome-to-lysosome sorting of EGFR, resulting in delayed receptor degradation and prolonged downstream signaling. We further demonstrate that ZNRF1 and c-CBL, another E3 ubiquitin ligase responsible for EGFR ubiquitination, mediate ubiquitination at distinct lysine residues on EGFR. Furthermore, loss of ZNRF1 results in increased susceptibility to herpes simplex virus 1 (HSV-1) infection due to enhanced EGFR-dependent viral entry. Our findings identify ZNRF1 as a novel regulator of EGFR signaling, which together with c-CBL controls ligand-induced EGFR ubiquitination and lysosomal trafficking.